PENGARUH PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL, KONDISI LINGKUNGAN KERJA, DAN WORK LIFE BALANCE TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN DI PT J RESOURCES BOLAANG MONGONDOW) - Saragih, Andreas Cahya Ucok Raya Persada; Lestari, Setyani Dwi (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
The purpose of this study was to determine whether industrial relations dispute resolution affects employee performance at PT J Resources Bolaang Mongondow, to determine whether work environment conditions affect employee performance at PT J Resources Bolaang Mongondow, to determine whether work-life balance affects employee performance at PT J Resources Bolaang Mongondow. The population consisted of 350 employees at PT J Resources Bolaang Mongondow. The sample in this study consisted of 78 respondents. The data was processed using the help of the SPSS 21 statistical analysis program. The results of the study showed that the resolution of industrial relations disputes had a significant influence on employee performance, the work environment had a significant influence on employee performance, and work life balance had a significant influence on employee performance.